Optimal Scheduling of Honeycomb Distribution Network Based on BADMM - Pengcheng ZHU; Zhaoyu LIU; Ke SUN; Jie XU; Pengfei HU; Daozhuo JIANG (Zhongguo dianli)
The honeycomb active distribution network is a new type of distribution network structure for large-scale microgrid clusters, which can realize efficient integration of large-scale distributed renewable energy. Aiming at the complex problem of the coordination operation between microgrids and smart power/information exchange stations (SPIES) in the honeycomb distribution network, this paper proposes a distributed optimal scheduling strategy based on block-wise alternating direction method of multipliers (BADMM) to minimize the operating cost. Firstly, a honeycomb distribution network optimization mathematical model is established according to the topology. And then the honeycomb distribution network is divided into multiple areas with SPIES as the center, and each SPIES coordinates and synchronously calculates the optimization problem of its adjacent microgrids, realizing the global optimization. Finally, the effectiveness and convergence of the proposed optimal scheduling strategy is verified by an example.